Moral culture - the basis of moral life - Muzaffarov, Samandar (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
In the article, man and his units are considered to be the creators and carriers of moral culture. There can be no moral life without aman. Therefore, attention is drawn to the fact that man and his units are the core of moral life, the main substantial element of moral culture that makes up the system, the creator, and carrier of moral culture from generation to generation. The article aims to identify and substantiate the objects of the formation of moral culture, the implementation of moral education processes